University teacher training in Spain: Evolution and perspectives - Pilar Aramburuzabala Higuera; Cynthia Martínez-Garrido; Rocío García-Peinado (Pontificia Universidad Católica del Perú, 2013)
In Spain, the first formal experiences in the field of University Teacher Training (abbreviated to FPU in Spanish) appear in the seventies, responding to isolated initiatives. In the eighties the first groups of FPU specialists are configured in scattered universities with the support of the government. Later, specialized departments arise that rely on the also emerging distance learning services and educational technology. Today, in a time when there are major changes in the university structure and the teaching models, it seems clear that the teaching and research staff will have to adapt to a very different environment. Thus, FPU becomes a powerful tool that can help improve the quality of university teaching and promote the professionalization of the teaching role. This article aims to make an approach to the experiences and research in the field of the FPU that were held in Spain from its origins. It also describes some of the emerging trends in the university system that will form the basis of a new University. This analysis will provide information to the debate on the professionalization of the teaching role that is currently taking place.